Strategi Pengembangan Produksi Kopi Robusta di Perumda Perkebunan Kahyangan Jember - Ahmad Muzayyin; Feti Fatiyah; Fadilatul Muharromah; Silviatul Jannah (CV. ITTC INDONESIA, 2024)
Coffee production in Indonesia increases every year. This increase occurred not only because of people's habits/traditions, but also because of changes in lifestyle/trends where coffee is in demand by all levels of society from various backgrounds. The background to this journal arises from the urgent need to respond to the complex dynamics in the robusta coffee industry, especially at the production level carried out by PDPKahyangan Jember. This research aims to explore strategies for developing robusta coffee production. The focus in this study is the identification and analysis of strategies that can be optimized by PDP Kahyangan Jember to increase productivity, efficiency and sustainability in robusta coffee production. The method used in carrying out this service is descriptive methodology. To identify problems in this research data, a qualitative approach was used. The result of this research is that a public company in the Jember kahyangan area is developing robusta coffee by producing robusta coffee through a very thorough processing process to produce quality coffee. There are several production processes and marketing processes for Kahyangan coffee, including taking raw materials, coffee roasting process, coffee milling, coffee packaging process, coffee product storage process, coffee product delivery, and marketing Kahyangan Jember coffee products.